HANG TUAH - THE NATION’S WARRIOR OF THE MALAY WORLD - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 15 October 2016 Hang Tuah is the warrior of the Malay world who needs to be immortalised in the minds of the masses. Based on various references including from the great literary works such as ‘Hikayat Hang Tuah’ and ‘Sulalat alSalatin’, Hang Tuah was truly a figure befitting such description